Opening new doors in autophagy research: Patrice Codogno. Issue 6 (2nd June 2016) - Codogno, Patrice; Klionsky, Daniel J.
ABSTRACT: Patrice Codogno (Fig. 1 ), one of the associate editors of Autophagy since it was established, is well known in the autophagy field, and has played a particularly important role in France, serving as the first president of Club Francophone de l'AuTophaGie (CFATG). Patrice's research career spans from the predominantly biochemical analyses that were commonly used in the 1980s to the molecular studies that are the primary focus of many labs currently studying autophagy today. Anyone who has met Patrice knows that he is modest, which means his contributions to autophagy and to promoting the careers of scientists globally, are underappreciated. In addition, there is a fun-loving side to Patrice that is often hidden to the casual observer, and it is time to share some of his personality and thoughts with the rest of the autophagy community.